Investigation of lab-scale horizontal subsurface flow constructed wetlands treating industrial cork boiling wastewater - Gomes, Arlindo Caniço (2018)
The feasibility and treatment efficiency of horizontal subsurface flow constructed wetlands (HSFCW) was assessed for the first time for cork boiling wastewater (CBW) through laboratory experiments. CBW is known for its high content of phenolic compounds, complex composition of biorecalcitrant and toxic nature. Two lab-scale units, one planted with Phragmites australis (CWP) and one unplanted (CWC), were used to evaluate the removals of COD, BOD, total phenolic compounds (TPh) and decolourization over a 2.5-years monitoring period under Mediterranean climatic conditions. Seven organic and hydraulic loading rates ranging from 2.6 to 11.5 g COD/m2/d and 5.7e9.1 L/m2/d were tested under average hydraulic retention time (HRT) of 5 ± 1 days required due to the CWB limited biodegradability (i.e., BOD5/ COD of 0.19). Average removals of the CWP exceeded those of the CWC and reached 74.6%, 91.7% and 69.1% for COD, BOD5 and TPh, respectively, with respective mass removals rates up to 7.0, 1.7 and 0.5 (in g/m2/d). Decolourization was limited to 35%, since it mainly depends on physical processes rather than biodegradation. CBW concentration of nine phenolic compounds ranged from 1.2 to 38.4 mg/L (for the syringic and ellagic acids, respectively) in the raw CBW, with respective removals in the CWP unit ranging from 41.8 to 76.3%, higher than those in the control unit. Despite CBWhigh concentration of TPhs (average of 116.3 mg/L), the HSFCW reached organic load removals higher than those of conventional biological treatment methods.